1996
DOI: 10.1111/j.1432-1033.1996.0121q.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Centrin Genes in Paramecium

Abstract: Centrins are highly conserved, ubiquitous cytoskeletal components which belong to the EF-hand superfamily of Caz+-modulated proteins. We report here the molecular characterization of new members of the centrin family, Paranzecium centrins. Previous studies described the organization of the infraciliary lattice (ICL), the innermost cortical cytoskeletal network of Paramecium, and showed that it was composed of a set of low-molecular-mass, Ca*+-binding polypeptides [Garreau de Loubresse, N., Klotz, C., Vigues, B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
57
0

Year Published

1997
1997
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 67 publications
(59 citation statements)
references
References 45 publications
2
57
0
Order By: Relevance
“…From the N-terminal peptide sequence of the centrin isoform ICL1, we characterised four nearly identical centrin genes: ICL1a, ICL1b, ICL1c and ICL1d (Madeddu et al, 1996). The frequent occurrence of such multigene families encoding nearly identical proteins in the Paramecium genome, finds its origin in the three successive rounds of whole genome duplication that occurred during Paramecium tetraurelia evolution (Aury et al, 2006).…”
Section: Resultsmentioning
confidence: 99%
“…From the N-terminal peptide sequence of the centrin isoform ICL1, we characterised four nearly identical centrin genes: ICL1a, ICL1b, ICL1c and ICL1d (Madeddu et al, 1996). The frequent occurrence of such multigene families encoding nearly identical proteins in the Paramecium genome, finds its origin in the three successive rounds of whole genome duplication that occurred during Paramecium tetraurelia evolution (Aury et al, 2006).…”
Section: Resultsmentioning
confidence: 99%
“…Although the gene of this 23-24-kD large contractile protein has been cloned in Paramecium (Madeddu et al 1996;Klotz et al 1997), detailed information on its potential phosphorylation is still required. In the Paramecium cortex, Abs against Ser/Thr phosphorylation sites recognize a variety of proteins of у20 kD (Keryer et al 1987), and cortical morphogenesis depends on the phosphorylation state of some basal body-associated proteins (Sperling et al 1991), as shown, e.g., in Figure 10.…”
Section: Can At the Infraciliary Latticementioning
confidence: 99%
“…The ICL of Paramecium is a Ca 2ϩ -associated contractile cytoskeletal network made of bundles of 4-nm filaments subtending the whole cell surface (1). In previous biochemical and genetic studies, we have identified, in addition to at least 10 centrin isoforms (12,24), a large centrinassociated protein (L-CAP; Ͼ350 kDa) as a major component of the ICL (20). We show here that L-CAP, hereinafter referred to as PtCenBP1p (for P. tetraurelia centrin-binding protein 1), is indeed an Sfi1p-like protein which presents the same remarkable succession of centrin-binding sites over the whole length of the molecule.…”
mentioning
confidence: 99%